Biometric canteen transaction system / Nurulshafika Umar - Umar, Nurulshafika (2016)
School canteen is the place that students usually go to buy some foods by using their pocket money. Nowadays, the school canteen sells too much of unhealthy foods which are not good for children’s health even though there are some restrictions from the ministry. In school canteen, the unhealthy foods that can be bought by students without the knowledge of parents are junk food, oily food and also carbonated drink. Parents are eager to know what their children eat at school; however, they cannot monitor the food intake since there is no medium provided for them. Each day, the children will be provided with cash money as in existing canteen management in school, every transaction is still using cash. The more cash money is being brought by children, the higher chances of them getting bullied at school. Hence, by implementing a web based system, it will provide a medium for parents to keep an eye on their children eating habit in school. This project is using Rapid Application Development (RAD) methodology. In order to reduce bully cases in school, fingerprint technology can be used. The students need to enrol and verify their fingerprint before they can purchase the food at the canteen. Thus, the children need not to bring pocket money to school. Dynamic graph representation is implemented in this project. Parents can choose the graph that they want to review by choosing the X and Y-axis of the graph. Parents also review the graph according to the date chosen. Thus, parents can monitor and control their children food intake and their children monthly expenses in school. By having this system, parents may be able to observe their children food intake in school. For future recommendation, the system can verify the fingerprint by just placing the finger on the fingerprint scanner, parents can view other type of graph instead of bar graph and the food can be categorized by its type.